(untitled) (Interdisciplinary Studies Journal, 2026)
This article analyzes the transposition of the North American concept of Not in My Backyard (NIMBY) into the context of Brazilian Condominium Law, investigating how the individual or collective resistance of co-owners to certain assembly deliberations, construction works, activities, or uses of common areas manifests legally and how the national legal order responds to such impasses. Drawing on civil and condominium law dogmatics, the study examines the tensions between the principle of private autonomy, the right to property (art. 5, XXII, of the 1988 Federal Constitution), the social function of property (art. 5, XXIII, CF; art. 1,228, §1, CC/2002), and the duties of coexistence imposed by statute and by the condominium convention. Through a dogmatic-analytical methodology comprising a bibliographical review of national and foreign civil law doctrine and an examination of precedents from the Superior Court of Justice and state Courts of Justice, the article demonstrates that NIMBY behavior in condominiums may constitute an abuse of rights (art. 187, CC/2002), an emulative act, or grounds for annulment actions of assembly resolutions. The work incorporates a comparative law perspective, examining solutions adopted in the North American, Portuguese, French, Spanish, and Italian legal systems. It is concluded that mediation, objective good faith, the principle of proportionality, and available procedural instruments constitute the central tools for overcoming these conflicts, with the strengthening of participatory and democratic culture in condominium deliberations being indispensable.